Experiences and needs of the caregivers of stroke survivors in Malaysia—A phenomenological exploration - Sidek, Norsima Nazifah; Kamalakannan, Sureshkumar; Tengku Ismail, Tengku Alina; Musa, Kamarul Imran; Ibrahim, Khairul Azmi; Abdul Aziz, Zariah; Papachristou Nadal, Iliatha (Frontiers in Neurology, 2022)
Introduction: Informal caregivers play a crucial role in supporting the activities of daily living, rehabilitation, and the road to recovery for stroke survivors. However, these informal caregivers are often reported as experiencing neglect and lack of recognition despite their primary contribution to stroke recovery. This study investigated the experiences of the caregivers of stroke survivors and access to stroke care in Malaysia. Method: This qualitative study with a phenomenological approach utilized in-depth interviews, including ten primary caregivers, one formal caregiver, and stroke healthcare providers as the participants. The interviews were done until the data saturation was achieved, and the data was analyzed using thematic analysis. Result: Three primary themes and 14 subthemes were identified from the interviews. The role of primary caregivers of stroke survivors had tremendous physical, mental and social impact on the caregivers. Caregivers had two primary needs. The need for information about comprehensive stroke care at home and the need for psychological support to themselves. The key internal driver for providing care was identified to be the motivation level of the stroke survivor and the external driver was identified to be the societal support with access to comprehensive stroke care. Conclusion: The role of informal caregivers becomes critical for continuum of stroke care. As caregivers take up the roles and responsibilities of those who contribute to stroke rehabilitation single-handedly soon after hospital discharge. Results of this study highlights the needs for providing systematic support to caregivers for engaging them in effective stroke care, particularly in the community. Stroke service providers, policy makers and program planners must be sensitized to empower caregivers of stroke survivors in effectively supporting stroke survivor in their family on the road of recovery.